2020
DOI: 10.1001/jamanetworkopen.2020.4207
|View full text |Cite
|
Sign up to set email alerts
|

Association of Socioeconomic Position With e-Cigarette Use Among Individuals Who Quit Smoking in England, 2014 to 2019

Abstract: IMPORTANCE e-Cigarette use among individuals who quit smoking more than 1 ago in England is highest among those with lower socioeconomic position and may affect smoking-related health inequalities, depending on whether the devices protect against relapse to tobacco smoking. OBJECTIVES To assess trends in current e-cigarette use by socioeconomic position among individuals who have quit smoking for at least 1 year, to capture postcessation initiation among those who quit within the past year and did not use an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Second, our study showed that some patterns of e-cigarette use in China differed from those in other countries. Particularly, previous nationally representative studies in the USA 23 and the UK 24 have indicated that e-cigarette use was highest among those with lower socioeconomic status. Interestingly, our study showed that e-cigarette use in China was more accepted by individuals with higher socioeconomic status, which is consistent with previous studies in Chinese population.…”
Section: Discussionmentioning
confidence: 92%
“…Second, our study showed that some patterns of e-cigarette use in China differed from those in other countries. Particularly, previous nationally representative studies in the USA 23 and the UK 24 have indicated that e-cigarette use was highest among those with lower socioeconomic status. Interestingly, our study showed that e-cigarette use in China was more accepted by individuals with higher socioeconomic status, which is consistent with previous studies in Chinese population.…”
Section: Discussionmentioning
confidence: 92%
“…Such results remind us of the dangers of safe assumptions and illustrate the likely complexity of e-cigarette effects. 7 Finally, the Kock et al 8 Of course, none of these studies yields definitive answers. For instance, all of them share the basic weakness that the various e-cigarette user groups were self-selected.…”
Section: Openmentioning
confidence: 99%
“…In addition to providing nicotine, e-cigarettes are believed to be able to change the habits of someone who is used to holding the cigarette to be smoked. E-cigarettes can help smokers to continue to consume cigarettes but without going through the burning process [ 15 ]. However, the use of e-cigarettes is still controversial.…”
Section: Introductionmentioning
confidence: 99%